Histamine induced high mobility group box-1 release from vascular endothelial cells through H1 receptor - Gao, Shangze; Liu, Keyue; Ku, Wenhan; Wang, Dengli; Wake, Hidenori; Qiao, Handong; Teshigawara, Kiyoshi; Nishibori, Masahiro (Frontiers in Immunology, 2022)
[Background] Systemic allergic reaction is characterized by vasodilation and vascular leakage, which causes a rapid, precipitous and sustained decrease in arterial blood pressure with a concomitant decrease of cardiac output. Histamine is a major mediator released by mast cells in allergic inflammation and response. It causes a cascade of inflammation and strongly increases vascular permeability within minutes through its four G-protein-coupled receptors (GPCRs) on endothelial cells. High mobility group box-1 (HMGB1), a nonhistone chromatin-binding nuclear protein, can be actively secreted into the extracellular space by endothelial cells. HMGB1 has been reported to exert pro-inﬂammatory effects on endothelial cells and to increase vascular endothelial permeability. However, the relationship between histamine and HMGB1-mediated signaling in vascular endothelial cells and the role of HMGB1 in anaphylactic-induced hypotension have never been studied. [Methods & Results] EA.hy 926 cells were treated with different concentrations of histamine for the indicated periods. The results showed that histamine induced HMGB1 translocation and release from the endothelial cells in a concentration- and time-dependent manner. These effects of histamine were concentration-dependently inhibited by d-chlorpheniramine, a specific H1 receptor antagonist, but not by H2 or H3/4 receptor antagonists. Moreover, an H1-specific agonist, 2-pyridylethylamine, mimicked the effects of histamine, whereas an H2-receptor agonist, 4-methylhistamine, did not. Adrenaline and noradrenaline, which are commonly used in the clinical treatment of anaphylactic shock, also inhibited the histamine-induced HMGB1 translocation in endothelial cells. We therefore established a rat model of allergic shock by i.v. injection of compound 48/80, a potent histamine-releasing agent. The plasma HMGB1 levels in compound 48/80-injected rats were higher than those in controls. Moreover, the treatment with anti-HMGB1 antibody successfully facilitated the recovery from compound 48/80-induced hypotension. [Conclusion] Histamine induces HMGB1 release from vascular endothelial cells solely through H1 receptor stimulation. Anti-HMGB1therapy may provide a novel treatment for life-threatening systemic anaphylaxis.